Предмет:
МатематикаАвтор:
elizavazquezАвтор:
rafaelbishopОтвет:
-8b
Пошаговое объяснение:
b(-2)+b(4-(-2)=(-8)b
Автор:
elodieb(x)=x*(4-x)/(x-2)
Сначала находим b(4-x):b(4-x)=(4-x)(4-4+x)/(4-x-2)
b(4-x)=x*(4-x)/(2-x)
Тогда:b(x)+b(4-x)=x(4-x)/(x-2)+x(4-x)/(2-x)=x(4-x)/(x-2)-x(4-x)/(x-2)=0
Ответ: 0Автор:
cupcakedkboДобавить свой ответ
Предмет:
Русский языкАвтор:
octavio15Ответов:
Смотреть
Предмет:
ГеометрияАвтор:
scruffypt9sОтветов:
Смотреть
Предмет:
Английский языкАвтор:
mallorycovxОтветов:
Смотреть
Предмет:
ФизикаАвтор:
miasybeardОтветов:
Смотреть